A gambling primary prevention program for students through teacher training: an evidence-based study. Issue 2 (4th May 2021) - Tani, Franca; Ponti, Lucia; Ghinassi, Simon; Smorti, Martina
ABSTRACT: Given the high prevalence of gambling among adolescents, the main purpose of the present study was to develop a gambling primary intervention program for students through the training of teachers about gambling-related knowledge and problems, and verify the effectiveness of the program in reducing gambling behaviors, cognitive distortions, and perception of gambling economic profitability in students. A total of 33 teachers (31.3% men) and 393 students aged 13 to 19 years (84% boys) were recruited for this study, randomly assigned to training (15 teachers; 219 students) and non-training groups (18 teachers; 174 students). An evidence-based longitudinal study designed with a pretest, and a follow-up after about 7 months, was conducted. Results showed that trained teachers improved their knowledge on gambling types and characteristics and related risks. The most relevant result was the impact the trained teachers had on their students, who reduced their gambling behavior, some cognitive distortions, and misconceptions related to the economic profitability of gambling. However, despite the relevance of these results, this study represents preliminary evidence, and further controlled studies are needed to confirm the possibility of using trained teachers as a less expensive method to efficiently prevent gambling among adolescents.